Efficacy and safety of curcumin in psoriasis: preclinical and clinical evidence and possible mechanisms - Zhang, Shuo; Wang, Jiao; Liu, Liu; Sun, Xiaoying; Zhou, Yaqiong; Chen, Siting; Lu, Yi; Cai, Xiaoce; Hu, Manqi; Yan, Ge; Miao, Xiao; Li, Xin (Frontiers in Pharmacology, 2022)
Background: Psoriasis is a chronic autoimmune inflammatory skin disease. Many studies have shown that curcumin (CUR) has strong anti-inflammatory effects and can improve psoriasis; however, its efficacy and safety have not been confirmed, and the specific mechanism remains to be elucidated. Objective: To evaluate the efficacy, safety, and possible action mechanisms of CUR in the treatment of psoriasis. Methods: The Cochrane Library, Embase, PubMed, Web of Science, China National Knowledge Infrastructure, Wanfang, and VIP (China Science and Technology Journal Database) were systematically searched for clinical trials and preclinical studies on the use of CUR in psoriasis treatment. All databases were searched from inception to January 2022. The meta-analysis was performed using RevMan 5.3 software. Results: Our meta-analysis included 26 studies, comprising 7 clinical randomized controlled trials and 19 preclinical studies. A meta-analysis of clinical trials showed that both CUR monotherapy and combination therapy improved PASI scores in patients compared to controls (standard mean difference [std.MD]: -0.83; 95% confidence interval [CI]: -1.53 to 0.14; p=0.02). In preclinical studies, CUR reduced the total PASI scores of psoriasis-like dermatitis mice compared to controls (std.MD: -6.50; 95% CI: -10.10 to -2.90; p=0.0004), the ear thickness (std.MD: -1.80; 95% CI: -3.20 to -0.41; p=0.01), and the expression of inflammatory cytokines such as interleukin (IL)-17 (std.MD: -1.35; 95% CI: -2.58 to -0.12; p=0.03), tumor necrosis factor (TNF)-α (std.MD: -3.82; 95% CI: -6.97 to -0.66; p=0.02), IL-17F (std.MD: -2.84; 95% CI: -5.04 to -0.64; p=0.001), and IL-22 (std.MD: -4.42; 95% CI: -7.31 to -1.52; p=0.003). In cell studies, CUR inhibited cell proliferation (std.MD: -3.88; 95% CI: -7.58 to -0.17; p=0.04) and the cell cycle (std.MD: -2.22; 95% CI: -4.24 to -0.21; p=0.03) and downregulated the inflammatory cytokines IL-6 (std.MD: -4.07; 95% CI: -6.31 to -1.83; p=0.0004) and IL-8 (std.MD: -4.19; 95% CI: -8.11 to -0.27; p=0.04). Conclusions: Our findings suggest that CUR is effective and safe for psoriasis treatment. The action mechanism of CUR against psoriatic dermatitis may be related to a reduced release of inflammatory factors (e.g., IL-17F, IL-6, IL-8, IL-22, and TNF-α) and cell proliferation and cell cycle inhibition.